Socjologia rodziny w Polsce - Tyszka, Zbigniew (Wydział Prawa i Administracji UAM, 1990)
The article contains the characterization of the development of the sociology of family in Poland, determines its basic notions and problems and presents main directions of research and its methodology. The author characterises the all-Polish programme of research on family, includes a summary of results obtained by Polish sociologists and presents main theses concerning the features of contemporary Polish families, their interactions with outside structures, the directions of their transformations and their internal processes. The dynamic development of the sociological research on family initiated in the end of the 1950s, has provided a detailed analysis of modern Polish families and offered valuable insights into the mechanisms of their evolution and the directions of changes.
The sociology of family in Poland